Avaliação da atividade mutagênica e antimutagênica da chalcona (E)-3-(4-nitrofenil)-1-fenilprop-2-en-1-ona - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
Chalcones represent a class of compounds that have attracted the interest of the scientific community due to the patchwork of biological activities related to them. This paper presents the evaluation of the mutagenicity and antimugenicity of a chalcone (E) -3 - (4-nitrophenyl)- 1-phenylprop-2-en-1-one in vivo micronucleus test in the mouse bone marrow. For the evaluation of mutagenic activity, the animals were treated with three different doses of chalcone (E) -3 - (4-nitrophenyl)-1-phenylprop-2-en-1-one (5, 10 and 20 mg / kg b.w.) and for the evaluation of the antimutagenic activity were administered the same doses (5, 10 and 20 mg / kg b.w.) concomitantly with a dose of 4 mg / kg of mitomycin C. The genotoxicity was evaluated by the frequency of micronucleated polychromatic erythrocytes (EPCMN) and cytotoxicity was analyzed by the polychromatic erythrocytes and normochromatic ratio (EPC / ENC). The results of the assessment of the mutagenicity showed that all doses of chalcone (E) -3 - (4-nitrophenyl)-1- phenylprop-2-en-1-one, significantly increased the number of EPCMN (p< 0.05) compared with the negative controls. Concerning the antimutagenicity capacity/ effect, all doses after 24 hours significantly reduced the frequency of EPCMN, for the positive control group (p <0.05). However doses of 5 and 10 mg / kg b.w. to be administered within 48 hours showed no antimutagenic activity (p> 0.05), while the dose of 20 mg / kg b.w. co-administered MMC enhanced the mutagenic action.
Keywords: Química Orgânica; Chalconas; Antitumoral das chalconas; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA